(untitled) (Revista de Ciências Agroveterinárias, 2020)
The objective of this study was to evaluate different menthol concentrations for the anesthesia of adult females, adult males, and juvenile guppy (Poecilia reticulata). To this end, 30 adult females (0.379 ± 0.108 g), 30 adult males (0.220 ± 0.049 g), and 30 juveniles (0.033 ± 0.016 g) were used. The animals were individually exposed to five concentrations of menthol (50, 100, 150, 200, and 250 mg L-1), six fish per concentration. The induction times, anesthetic recovery, and mortality up to 96 h after the experiment were evaluated. The concentration of 50 mg L-1 did not induce anesthesia in any of the studied groups. The concentrations of 100 and 250 mg L-1 resulted in 100% mortality in the adults (male and female) and juveniles, respectively. The concentrations from 150 to 250 mg L-1 and from 150 to 200 mg L-1 of menthol were efficient and safe for use as anesthesia for guppy adults (male and female) and juveniles, respectively.